The Onset of Feedback in A1885: Evidence for Large-scale Quenching Despite a Young Central Active Galactic Nucleus - Laurel White; Michael McDonald; Francesco Ubertosi; Massimo Gaspari; Julie Hlavacek-Larrondo; Helen Russell; Taweewat Somboonpanyakul (The Astrophysical Journal, 2025)
We present a new 8.5 ks Chandra observation of A1885 ( z = 0.089), obtained as part of the Cluster Evolution Reference Ensemble At Low- z (CEREAL) survey of ∼200 low- z galaxy groups and clusters. These data reveal that A1885 is a strong cool core, with a central cooling time of $0.4{3}_{-0.04}^{+0.12}$ Gyr, and that the central galaxy hosts an X-ray-luminous point source at its center ( L ${}_{2-10\,keV}\,=2.{3}_{-0.7}^{+0.9}× 1{0}^{42}$ erg s ^−1 ), indicative of a rapidly accreting supermassive black hole (SMBH). In the context of the larger CEREAL sample, we constrain the fraction of clusters at z ∼ 0.15 with X-ray-bright ( L _2−10 > 10 ^42 erg s ^−1 ) central active galactic nuclei (AGN) to be no more than 4.1% at 95% confidence. Including radio data from LOFAR, the Giant Metrewave Radio Telescope, ASKAP, and the Very Large Array, spanning 44 MHz–150 GHz, and optical integral field unit data from the Sloan Digital Sky Survey's MaNGA, we probe the details of cooling, feeding, and feedback in this system. These data reveal that cooling of the intracluster medium is highly suppressed on large (>10 kpc) scales despite a central SMBH that is in the early stages of the self-regulation cycle (characterized by rapid accretion, physically small jets, and no large-scale low-frequency radio emission). To reconcile the large-scale quenching with a lack of visible large-scale feedback, we propose that the timescale on which energy is dissipated on large scales (>10 kpc) is significantly longer than the timescale on which black hole feeding operates on small (∼parsec) scales. This interpretation disfavors a model in which the energy is rapidly dissipated (e.g., shocks), which would synchronize the feeding and feedback timescales, and favors a model in which the heating effects of AGN feedback can linger long after the outburst has passed (e.g., turbulent mixing).